Degradable multi(aryl azide) star copolymer as universal photo-crosslinker for elastomeric scaffolds. (June 2019) - Gangolphe, L.; Déjean, S.; Bethry, A.; Hunger, S.; Pinese, C.; Garric, X.; Bossard, F.; Nottelet, B.
Abstract: Degradable elastomers with elastic properties close to those of soft tissues are necessary for tissue engineering. Most degradable elastomers developed so far are based on functional low–molecular-weight prepolymers that are combined with molecular crosslinkers to yield the elastomeric three-dimensional networks. To overcome this limitation, we present in this work the concept of star-shaped macromolecular multi(aryl azide) photo-crosslinker that has the ability to efficiently cross-link any polymer containing C-H bonds independently of its molecular weight and without the need for prefunctionalization. This concept of universal crosslinking agent is illustrated with a star-shaped block copolymer composed of an 8-arm poly(ethylene glycol) core and poly(lactide) side arms functionalized with aryl azide moieties (PEG8arm -PLA-fN3 ). It was selected due to its macromolecular nature that allows for an easy processing of electrospun photo-crosslinked scaffolds, while making it possible to adapt its chemical nature with one of the polymer matrices. A parameter study is first carried out on PEG8arm -PLA-fN3 /PLA-Pluronic ® -PLA films to evaluate the impact of the polymers' molecular weight, PEG/PLA ratios, and UV irradiation conditions on the crosslinking efficiency. This study confirms that high crosslinking efficiencies can be obtained with PEG8arm -PLA-fN3 (60%) compared with commercially available bis(aryl azide) photo-crosslinker (below 15%). Optimal conditions are then used to yield electrospun microfibers (1–2 μm) crosslinked with PEG8arm -PLA-fN3, resulting in biocompatible and highly elastomeric scaffolds ( ε y > 100 % ) compared with uncrosslinked scaffolds ( ε y < 10 % ). In addition, we show that the degradation rate can be controlled overtime depending on the blend content of PEG8arm -PLA-fN3 . Taken together, these results demonstrate the potential of macromolecular multi(aryl azide) photo-crosslinkers to develop original degradable elastomeric scaffolds for soft tissue reconstruction. Highlights: Star-shaped multi(aryl azide) copolymers as universal macromolecular photo-crosslinkers. Polymer-independent photo-crosslinker turns polymers into degradable network. Crosslinked electrospun fibers are easily generated yielding elastomer scaffolds. Mechanical and degradation properties are modulated by the content of the macromolecular photo-crosslinker.